A formação continuada dos professores dos anos finais do Ensino Fundamental da rede pública do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This is a doctoral research of the Postgraduate Program in Education of the State University of Ponta Grossa and its object of study is the continuing education of teachers in the public school system of Paraná. It comes from the theses that although the current policies of continuing teacher education at the state level of a neoliberal, pragmatic, standardized and performative nature are assigned to the state education network, there are schools that through the integration of their teaching and pedagogical teams manage to promote continuing teacher education takes place in the school context, considering the reality of the teachers, their needs and wishes, enabling their professional development. Its guiding question is: How does the continuing education of teachers of the final years of elementary school in the public schools of Paraná take place and what is its relation to the professional development of teachers? It aims to know the proposal of continuing education offered by the State Department of Education and Sports of Paraná to teachers of the final years of elementary school; to discuss how the continuing education of teachers of the final years of elementary school in public schools of Paraná occurs; and to unveil the possibilities of professional development of teachers of the final years of elementary school through the continuing education offered in the school in the public system of Paraná. The research, qualitative in nature, documentary and exploratory, was based on the praxiology of Pierre Bourdieu (2003, 2004, 2011, 2013), the conception of professional development and continuing education were supported by João Formosinho (2009, 2014). Data were produced through the application of online questionnaires sent to pedagogues and teachers of Portuguese and mathematics who work in the final years of elementary school in Paraná, and through semi-structured interviews conducted in person or remotely. The four participating schools were selected based on the highest indicators of the State Basic Education Development Index, in 2019, as well as the subject of activity of the participating teachers, which integrate such indicator. The data were treated through Content Analysis (BARDIN, 2016), raising four categories that encompass teacher training on its own, the specificities of the schools surveyed, the continuing education and the professional development in context and teacher training policies of the state education network of Paraná. It appears that the training provided by the government of Paraná with a focus on results and improvement of educational indicators is refuted by the schools surveyed. Pedagogical teams and teachers prefer to carry out continuing education related to the school reality rather than following in full what is proposed by the State Department of Education. However, this process can be improved with in-context training anchored theoretically in the perspective of educational praxis together with universities and entities associated with scientific research.
Keywords: Formação Continuada; Desenvolvimento Profissional; Formação em Contexto; Continuing Education; Professional Development; In-context training; CNPQ::CIENCIAS HUMANAS::EDUCACAO